Effects of diet manipulation on growth performance, carcass characteristics, and meat quality of intact male pigs - C A Maloney; Robert H Hines; H Cao; J S Park; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1998)
Castrates were predictably less efficient, had greater ADFI, and tended to have more BF than contemporary boars. Castration decreased detection of boar taint, but alterations of dietary CP, pH, and antimicrobial level from 225 to 276 lb had no effect on sensory panel perception of odor from fat of intact males.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Boars; Diet; Boar odor